ANALISIS FINANSIAL USAHA PERIKANAN TANGKAP IKAN TUNA DI PPP PONDOKDADAP KABUPATEN MALANG - Yeni Sari Wulandari (CV. ADIBA AISHA AMIRA, 2023)
South Malang is one of the areas that has a major influence on capture fisheries in Indonesia. Based on data from the Malang Regency Fisheries Service in 2018, PPP Pondokdadap catches tuna by Sendang Biru fishermen around 100 tons per day, besides that PPP Pondokdadap is also a supplier of tuna for export factories located in Bali, Jakarta, Probolinggo and markets throughout Indonesian territory. Tuna fish turns out to be a fishery commodity that contributes to an increase in exports with a value above the average of 18.57%. This is an opportunity for Indonesia to improve the country's economy by utilizing existing fishery resources. There is this great potential, but fishermen have not yet calculated the overall financial analysis of the tuna fishing business. The aim of this research is to know the feasibility of tuna fishing business. This research was conducted in August-November 2019 with fishermen at PPP Pondokdadap, Malang Regency. The data analysis method used in analyzing the feasibility of this business is financial analysis based on NPV, Net B/C, IRR and PP.